2017
DOI: 10.3390/polym9020041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fumed Silica and Draw Ratio on Nanocomposite Polypropylene Fibers

Abstract: Abstract:Hydrophylic fumed silica AR974 was tested as a potential nanofiller for the production of composite isotactic polypropylene filaments/fibers (containing 0.25-2 vol % of nanoparticles) via melt compounding and subsequent hot drawing. The objectives of this study were as follows: (i) to investigate the effects of the composition and the processing conditions on the microstructure and the thermal and mechanical properties of the produced fibers; (ii) to separate the effects of silica addition from those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
2
15
0
1
Order By: Relevance
“…The effective particle volume fraction φ e generally increased with the filler content, evidencing a relative minimum at 4 vol%. On the other hand, the large initial decrease of the B parameter suggested that the extent of the particle agglomeration increased, as previously determined also in nanocomposite polyolefin fibers with hydrotalcite [69] or fumed silica [32]. However, above 4 vol% the B parameter exhibited an almost constant value until 24 vol% of fumed silica, suggesting a relatively minimum level of aggregation in the tested composition range, in agreement with the results of morphological analysis (see Figure 1).…”
Section: Monofrequency Dmta Analysis and Vicat Gradesupporting
confidence: 90%
See 1 more Smart Citation
“…The effective particle volume fraction φ e generally increased with the filler content, evidencing a relative minimum at 4 vol%. On the other hand, the large initial decrease of the B parameter suggested that the extent of the particle agglomeration increased, as previously determined also in nanocomposite polyolefin fibers with hydrotalcite [69] or fumed silica [32]. However, above 4 vol% the B parameter exhibited an almost constant value until 24 vol% of fumed silica, suggesting a relatively minimum level of aggregation in the tested composition range, in agreement with the results of morphological analysis (see Figure 1).…”
Section: Monofrequency Dmta Analysis and Vicat Gradesupporting
confidence: 90%
“…Due to its morphological properties, this nanofiller is able to self-aggregate when dispersed in polymer matrices, forming an interconnected network of interacting particles. The role played by silica nanoparticles with different thermoplastic matrices and the consequent thermo-mechanical behavior of nanocomposites produced firstly by melt-compounding and then either by compression molding [23][24][25][26][27][28][29][30] or by fiber spinning [31,32] was extensively investigated by our group in the last years. It was demonstrated how nanosilica addition leads to a strong stiffening effect on the polymer matrices, without impairing their failure properties, improving also the dimensional and thermal degradation stability.…”
Section: Introductionmentioning
confidence: 99%
“…The T max values of this study are in the same range and slightly higher than respective literature values. For example, for PP-fumed silica drawn fibers, values from 300 • C for neat PP up to 330 • C for the composite fibers with 1% silica [39] were reported. For organically modified montmorillonite, values of 348 to 387 • C for T max were reported [40].…”
Section: Thermal Stability Of Pp Composite Drawn Fibersmentioning
confidence: 99%
“…This phenomenon is clearly observable in Figure 9A, which displays the trend of the tensile modulus as a function of DR for melt-spun PP fibers [109]. As the draw ratio increases, a severe increment of the fiber stiffness can be observed; furthermore, as documented by the results depicted in Figure 9B, a concurrent increment of the tensile stress and a drastic decrease of the fiber ductility verify as a consequence of drawing.…”
Section: Effect Of Elongational Flow In Modifying Morphology and Mechanical Properties Of Homogeneous Polymersmentioning
confidence: 73%